Government pay and perks: growing chaos - Joseph, K.P. (1999)
The national pay scene is very chaotic and full of anomalies, many of them legacies of history. Government employees now enjoy several unintended benefits which originated during British rule plus numerous concessions unique to India that have been wrested by them through agitation. An objective survey that will be equally fair to the government employees and the public that pays them is immediately needed to bring out the many excesses and to remove them. - Reproduced
Keywords: Civil service - Salaries, etc; Civil service - India; Civil service